PENGEMBANGAN MEDIA PEMBELAJARAN LUMI EDUCATION BERBASIS PROJECT BASED LEARNING PADA MATERI EKOSISTEM - Hanafi Arbi Wiranata; M. Nasir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop Lumi Education learning media based on Project Based Learning (PjBL) on ecosystem material for junior high school/Islamic junior high school students as an effort to improve the quality of science learning that is more interactive, innovative, and student-centered. Ecosystem material is often considered difficult to understand because many concepts are abstract and require real visualization so that students can more easily understand the relationship between ecosystem components. This study uses the Research and Development (R&D) method with the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The media was developed using the Lumi Education platform with H5P integration that contains interactive videos, images, animations, learning evaluations, and project-based activities. The application of the Project Based Learning model allows students to be more active in the learning process through observation, discussion, and project completion related to ecosystem material. The results of media validation were carried out by media expert validators and material experts using a Likert-based validation instrument analyzed using the Aiken's V formula. The results showed that the learning media obtained a valid category with an average Aiken's V value of 0.81. The design, pedagogy, content, and technical aspects received good ratings, thus declaring the media suitable for use in science learning. Lumi Education's project-based learning media for ecosystems is expected to enhance student motivation, critical thinking skills, creativity, and a deeper and more contextual understanding of ecosystem concepts.